Aesthetics and spirituality in the Australian services sector - Issa, Theodora; Pick, David (Emerald Group Publishing Limited, 2010)
Purpose - the purpose of this paper is to report on the results of research focusing on the relationships between aesthetics and spirituality in the Australian services sector. Design/methodology/approach - the research employs an interpretive mixed-method approach. The data were collected using an online survey developed from a range of existing research tools. The population of interest is employees in the Australian services sector. The results were analysed using quantitative and qualitative data analysis techniques.Findings - the results of the analysis suggest that people who work in the Australian services sector tend to consider themselves "spiritual", but it is a spirituality that is not necessarily religious, it might more likely be derived from aesthetics.Research limitations/implications - The main limitation of this study is the small sample size, which limits the inferences that can be drawn. Despite this limitation, this study has important implications in that it illuminates and attempts to resolve some of the conceptual confusion and contradictions in the existing literature relating to aesthetics and spirituality that has no connection with religiosity and spirituality be equated with expressed religious beliefs.Originality/value - This paper presents an investigation of the relatively neglected area of spirituality and aesthetics in the context of th Australian business environment and stimulates the debate about spirituality and aesthetics in the workplace.